A Study On Attitude Of Youth Towards Skills Development Programs, Hyderabad - M, Harinder; Ayesha (International Journal of Psychosocial Rehabilitation, 2019)
India is in a demographic dividend phase, with half the total population being in the working-age group as of 2011 and will be in this zone for over two decades. This phase is expected to last till 2055. According to Economic Survey 2018-19, India’s Demographic Dividend will peak around 2041, when the share of working-age, i.e. 20-59 years, population is expected to hit 59%. The continuing demographic dividend in India could add about two percentage points per annum to India’s per capita GDP growth over the next two decades. India is in a demographic dividend phase, with half the total population being in the working-age group as of 2011, and will be in this zone for over two decades. This phase is expected to last till 2055. The continuing demographic dividend in India could add about two percentage points per annum to India’s per capita GDP growth over the next two decades. While technical and soft skills are a prerequisite for any job seeker, what is more significant to get an edge is the right attitude. A candidate lacking certain skills can be trained to acquire those skills after recruitment as long as he has the right attitude. Literature: The objective of the paper is to understand and analyze the challenges of skill development among the small tea growers. The test result of data on Chi Square for 60 respondents indicates that skill development is very crucial for the performance of the workers. Methodology: 60 simple random sampling method and size is used for the present study. Results: The majority of the respondents were between 21 to 23 years of age, Unmarried, earning less than Rs.1,00,000/- and from joint family. Majority of the respondents who were married belonged to nuclear families, have medium level of decision making capacity. Chi-square test was used to test the significance in variables. There is no significance between Age and Learning abilities with chi-square value 0.024. There is no significance between Marital status and Decision making capabilities with chi-square value 0.046. There is significant association between Marital status and Employment with chi-square value 0.02.